A Systematic Review of Suicidality in People with Intellectual Disabilities. Issue 3 (May 2016) - Dodd, Philip; Doherty, Ailbhe; Guerin, Suzanne
Abstract: Background: Suicidality in people with intellectual disability has not been extensively researched. Aim: To identify the nature of the research that has actually been conducted on this topic. Method: A search of research databases was conducted according to predefined criteria. Key information was extracted and rated for methodological merit. Results: Twenty-four studies met the inclusion criteria for this systematic review. The aspects of suicidality investigated, which varied among studies, included suicidal attempts, behavior, ideation, and completed suicide. Thirteen studies highlighted risk factors for suicidality in this population. The most frequently noted risk factors were a concurrent mental health difficulty and the level of intellectual disability. Eight studies referred to people with intellectual disabilities' understanding of the concept of death or suicide. Various methodological issues were identified in the studies included. Conclusions: In what we believe to be first systematic review of suicidality in people with intellectual disabilities, it was apparent that well-designed, standardized research studies on the topic are scarce. There is consequently limited evidence to guide prevention and intervention strategies for suicidality in this population.